Analysis on Optimization of Agricultural Products Supply Chain Based on Dynamic System - Yuhan Guo; Yue Yin (Discrete Dynamics in Nature and Society)
To thoroughly implement the spirit of the Fifth Plenary Session of the 19th CPC Central Committee, this paper optimizes the supply chain of agricultural products based on dynamic system. In the complex supply chain of agricultural products, they are scattered upstream and downstream. It is difficult to form agglomeration scale effect, information asymmetry between supply chain nodes, and poor hardware environment of supply chain. Logistics operation is difficult. By analyzing the supply chain of agricultural products, optimize the supply chain by using the push-pull supply chain. According to the change of market demand, the push mode and the pull mode are properly allocated and the government’s attention to the supply chain is increased, intentionally the Internet is combined with the supply chain, the stability of the supply chain is increased, and there is a certain adaptability to market demand fluctuations. Problems can be fed back to the suppliers and final buyers of agricultural products in time, and the delivery rate of the whole supply chain should be improved.